THE ANALYSIS OF ISLAMIC FAMILY LAW ON PARENTING PATTERNS AT AL-IKHLAS ISLAMIC BOARDING SCHOOL TALIWANG AS A FORM OF CHILD RIGHTS PROTECTION - Nafisah, Fiddha; Tahir, Masnun (Hukum Islam, 2024)
This study analyzes the aspects of family law in Islam related to parenting in Islamic boarding schools as a form of protection of children's rights, with a case study at Al-Ikhlas Islamic Boarding School, Taliwang District, West Sumbawa Regency. This research focuses on two main aspects, namely how the parenting style in the Al-Ikhlas Islamic Boarding School is applied and how the Islamic family law analyzes the parenting style. Using a qualitative research approach with empirical methods, data were collected through interviews, observations, and documentation. The results of the study show that the parenting style at the Al-Ikhlas Islamic Boarding School involves 24-hour parenting as a means of education and the implementation of the "Demerit Point" system which functions as a step to protect children's rights by replacing physical punishment with educational punishment. This parenting style is considered to be in accordance with Islamic teachings that prohibit acts of violence, although there are still cases of violence that are still handled seriously.